Dietary protein requirements of older adults with sarcopenia determined by the indicator amino acid oxidation technology - Wu, Wenxuan; Chen, Fengge; Ma, Hui; Lu, Jiaxi; Zhang, Yanhong; Zhou, Haisong; Yang, Yunqi; Nie, Shuhui; Wang, Rui; Yue, Weixiao; Li, Min; Yang, Xiaoguang (Frontiers in Nutrition, 2025)
BackgroundAlthough protein supplementation may be desirable in the management of sarcopenia, the appropriate protein requirements for older adults with sarcopenia are presently unclear.ObjectiveThe aim of this study was to determine the protein requirements of older adults (65–81 year) with sarcopenia by using the indicator amino acid oxidation (IAAO) technology.MethodsNine older adults with sarcopenia (four male participants and five female participants) participated in the study, with protein intakes ranging from 0.1 to 1.8 g/(kg·d). Each participant consumed an adapted diet with a protein level of 1.0 g/(kg·d) and 1.7 resting energy expenditure (REE) for 2 day. Day 3 was the oxidation day of the study. Diets that delivered energy at a 1.5 × REE were isocaloric. The amounts of phenylalanine and tyrosine maintained at a constant across intakes. Therefore, phenylalanine and tyrosine were added to the protein doses of 0.1–1.5 g/kg, which was based on the highest dose of lactalbumin content [1.8 g/(kg·d)]. Applying a non-linear mixed-effects model analysis of F13CO2, the protein requirement was determined by identifying the breakpoint in the F13CO2 data with graded amounts of dietary protein.ResultsThe mean estimated average requirement (EAR) and recommended nutrient intake (RNI) of protein for older adults with sarcopenia were 1.21 (95% CI: 0.95, 1.46) and 1.54 (95% CI: 1.13, 1.95) g/(kg·d), respectively.ConclusionsTo our knowledge, this is the first study of protein intake in older adults with sarcopenia and indicates that older adults with sarcopenia may require a higher intake of dietary protein.Clinical trial registrationhttp://www.chictr.org.cn, ChiCTR2200061383.